Chemo-, regio- and stereo-selective aerial oxidation of limonene to the endo-1,2-epoxide over Mn(Salen)-sulfonated SBA-15 - Saikia, Lakshi; Srinivas, D.; Ratnasamy, Paul (Applied Catalysis A-General, 2006)
Mn(Salen) complexes immobilized on sulfonic acid-functionalized SBA-15 molecular sieves (SBA-15-pr-SO3-Mn(Salen)) catalyze the Mukaiyama-type oxidation of R-(+)-limonene selectively to the 1,2-epoxide with molecular oxygen at 298 K (Salen = N,N-ethylenebis(salicylidenaminato)). The endo-diastereomer is formed with a diasteromeric excess of 39.8%. This catalyst exhibited higher catalytic activity than ``neat'' Mn(Salen) complexes directly supported on SBA-15 or zeolite-Y. A change in the oxidation state of Mn from +3 in the ``neat'' complex to +2 when immobilized on the sulfonated surface is a probable cause for the observed enhancement of catalytic activity. A part of the Mn complexes was leached out of the solid phase during the reaction. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: aerial oxidation of limonene; catalysis by Mn(Salen) complexes; chemo-; immobilized Mn Schiff base complexes; Mesoporous molecular sieves; Mukaiyama-type oxidation; regio- and stereo-selective epoxidation; sulfonic acid-functionalized SBA-15